The risk factor of urinarytract infection in patient with leukemia - Pungky Ardani Kusuma, Melati Dini Hari, Soetaryo, (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Urinary tract infection (UTI) is one of most common infectious diseases in patients wuth leukemia. Some researchers showed that the prevalence of UTI was the third highest after pneumonia and gastrointestinal tract infection among children with leukemia. UTI may be affected by many factors, i.e. host, microorganism, and environment. E. coli, Klebsiella, dan Proteus are the most common bacterial etiology of UTI in leukemia. Objective: The aim of this research was to know the risk factor of UTI in children with leukemia. Method: This research used case-control design. Subjects of this study were children (0-15 years old) with leukemia who came to Department of Pediatrics, Dr. Sardjito Hospital since January st, 2000 until October 3", 2008. There were 38 patients in case group and 109 patients in the control group. Data collected from medical records were age, gender, nutritional status, type of leukemia, treatment phase of leukemia, and absolute neutrophil count. Risk factors analyzed were age, gender, nutritional status, and neutropenia. UTI was diagnosed by bacterial culture and bacterial count. Result: Univariate analysis showed that female gender was the risk factor of UTI (OR 2.35; CI 1.10- 5.00), meanwhile age less than 5 years old (OR 0.48; CI 0.22-1.06L poor-fair nutritional status (OR 1.20; CI 0.52-2.78), and neutropenia (OR 0.73; CI 0.35-1.55) were not risk factors of UTI. Multivariate analysis showed that female gender was the risk factor of UTI (OR 2.36; CI 1.08-5.14). Conclusion: Female gender was a risk factor of UTI in children with leukemia Keywords: leukemia - children - gender - urinary tract infection - risk factors